Desafíos Y Adaptación De La Profesión Contable Ante La Automatización Impulsada Por La Inteligencia Artificial (2024)
The purpose of this research project is to analyze the challenges generated by the arrival of AI in accounting practice and the adaptation strategies needed to face these changes. Artificial intelligence has experienced a great advance in recent years, which has made it possible to automate some tasks that were previously performed by professionals. Nonetheless, the accounting profession is thought to be broad and complex, and while AI can take care of repetitive tasks, there are many others that require specialized skills and knowledge that only a professional can provide. This research seeks to contribute knowledge to the academic and professional field about this new technological era that has been taking place with the presence of artificial intelligence and how it is being included in the accounting profession. The methodology by which the research was carried out is descriptive, the primary research tools are constituted by the elaboration of surveys aimed at students and teachers of public accounting, while the secondary information tools are constituted by the various investigative means that will be essential to obtain pertinent information and enrich the research. among which are: Documents, websites, and repositories. The research reveals how artificial intelligence is transforming, rather than replacing, the role of the accounting professional towards more analytical and strategic activities. Emerging technology is identified as an instrument that, if properly exploited, can enhance the efficiency of accounting processes, allowing professionals to focus on analysis and decision-making, beyond routine tasks. It was concluded that, to successfully navigate this evolving landscape, accounting professionals must take a proactive approach towards learning and skill development. This includes not only technical capabilities directly related to artificial intelligence and automation, but also those soft skills that enable effective adaptation to change and the ability to add value through the strategic interpretation and application of financial data.